Credibility and the Critique of the Theory of the Veritable Nature of Human Sciences with Emphasis on Jurisprudence and Law - Mohammad Reza Asadi; Seyed Saieed Lavasani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The theory of conventions is the basis of Islamic humanities, if it is viewed from a philosophical and holistic perspective and taken as part of existential discussions. In reality, humans are genuine and real beings that express their needs in this world through the language of conventions. Therefore, conventions are intertwined with anthropology and epistemology and act as the pillars of Islamic humanities. Propositions in the humanities including propositions in jurisdiction and law are conventions and do not necessitate proofs. What is important in these sciences is to attract benefits and dispose loss and gain perfection and prosperity, and in Islamic humanities the aim is to reach closeness to Allah. But, those who take jurisprudence and legal propositions as genuine have mixed genesis and decree since genuine relationships exist in areas where there is a relationship between cause and effect. In jurisprudence and legal issues, a law is validated through a judge and has no genesis, and religious or customary laws are taken from the validity of the judge or a legislator.